2015
DOI: 10.1016/j.otsr.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and complications associated with thenar and standard portals during arthroscopic surgery of thumb carpometacarpal joint

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…5 A more user-friendly portal, the thenar portal, was proposed for improving the view and better performance of the procedures in the CMC joint. 2,[4][5][6][7] The portal seems to be safe because only mild complication was reported (transient scar tenderness). 7 However, the periportal anatomy has not been well elucidated, and the published data delineating the relationships between the MBMN and its terminal branches and the thenar portal were seldom found.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…5 A more user-friendly portal, the thenar portal, was proposed for improving the view and better performance of the procedures in the CMC joint. 2,[4][5][6][7] The portal seems to be safe because only mild complication was reported (transient scar tenderness). 7 However, the periportal anatomy has not been well elucidated, and the published data delineating the relationships between the MBMN and its terminal branches and the thenar portal were seldom found.…”
Section: Discussionmentioning
confidence: 98%
“…2,[4][5][6][7] The portal seems to be safe because only mild complication was reported (transient scar tenderness). 7 However, the periportal anatomy has not been well elucidated, and the published data delineating the relationships between the MBMN and its terminal branches and the thenar portal were seldom found. Walsh et al 5 reported that MBMN was an average of 23 mm from this portal, however, which point of the MBMN to the portal measured was not described.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This rate could be reduced by using the thenar approach 35,36 to the TM joint, which appears to be less risky than the conventional approach. [37][38][39] In addition, it would be interesting to compare our technique with other techniques, such as suspensionplasty, with or without the addition of adipose stem cells.…”
Section: Discussionmentioning
confidence: 99%